Estimation of surface displacements caused by landslides in Huancabamba, Piura, using satellite images during the period 2017-2019 - Alayo Ontón, Joel Telmo (2021)
In this study we analyze and estimat the surface displacements produced by landslides in the Huancabamba city and surroundings, applying subpixel correlation processes (based on Fourier transforms) to satellite optical images (SPOT 6 and Sentinel 2) for the period 2017-2019. The results show 14 areas of greater surface deformation, distributed in the study area. Eleven zones show displacement magnitudes between 0.17 m and 0.83 m, with propagation velocities between 0.2x10-5 mm/s and 2.8x10-5 mm/s. While 3 zones located within urban area show some instability depicted by slow but continuous displacements with magnitudes ranging from 0.10 m to 0.25 m and velocities of 1.6x10-6 mm/s and 4.9x10-6 mm/s. To validate and correlate the results, we analyze GPS displacements measured at campaign sites and morphodynamic aspects; as well as the occurrence of local and regional seismicity and precipitation rates. This study allowed to generate and provide technical information useful to identify hazardous zones in and around Huancabamba, which serves as input for the characterization of unstable and prone to landslides, contributing to disaster risk management in that locality.